Construction project management a practical guide to field construction management - Sears, S. Keoki (Wiley, 2008)
This volume provides a guide to managing all aspects of a construction project. This is a new edition of this guide to the subject which includes a new chapter devoted solely to the planning process and another on legal aspects of scheduling.